RISK FACTORS FOR THE DEVELOPMENT, PREDICTION AND PREVENTION OF GESTATIONAL AND PERINATAL COMPLICATIONS DUE TO ADENOMYOSIS - Akhmedjanova Kh.Z. (Journal Park Publishing, 2025)
Department of Obstetrics and Gynecology Tashkent Medical Academy Annotation Achieving favorable gestational and perinatal outcomes in women with adenomyosis is extremely important. The purpose of the study was to determine the pathogenetic role of adenomyosis in the development of obstetric and perinatal complications to improve the method of treating pathology with pre-conception preparation and to develop a prediction method complication during gestation.
Keywords: Adenomyosis, complications of pregnancy and childbirth, prevention of pregnancy complications Relevance. In the Republic of Uzbekistan, as in other countries of the world, issues of maternal and child health are one of the priority areas of modern medicine [2,5]. Today, women's reproductive health is considered as the most important general medical and social problem, which is the focus of constant attention of the world's leading scientific centers.